2010
DOI: 10.1097/mol.0b013e32833cacd5
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor-dependent lipid body formation in macrophage foam cell formation

Abstract: TLR stimulation promotes the accumulation of lipid bodies in macrophages and consequently foam cell formation. The pathways responsible for these processes may constitute novel therapeutic targets for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
2
26
0
1
Order By: Relevance
“…Previous studies by our and other laboratories have shown that the activation of macrophages with LPS and other TLR activators increases macrophage TG accumulation ( 29,30 ). We therefore next examined the effect of have failed to demonstrate that niacin therapy when added to statins reduces cardiovascular disease events (34)(35)(36).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Previous studies by our and other laboratories have shown that the activation of macrophages with LPS and other TLR activators increases macrophage TG accumulation ( 29,30 ). We therefore next examined the effect of have failed to demonstrate that niacin therapy when added to statins reduces cardiovascular disease events (34)(35)(36).…”
Section: Downloaded Frommentioning
confidence: 99%
“…21,43,[47][48][49][50][51] First, TLRs induce foam cell formation by increasing the uptake of lipoproteins and the storage of lipid (via increases in CD36, AP2, fatty acid-binding proteins, MyD88-adaptor-like, adipose differentiation-related protein, lipin 1, glycerol-3-phosphate acyltransferase 3, and diacylglycerol O-acyltransferase 2). 52,53 Second, TLRs decrease the delivery of cholesterol macrophages to high-density lipoprotein (HDL), the first step in reverse cholesterol transport (via decreases in macrophages ATP-binding cassette transporter subfamily A (ABCA)-1, ATP-binding cassette transporter subfamily G, scavenger receptor class B, member 1/CD36 antigen-like 1, and apolipoprotein E). [54][55][56] The HIV Nef gene is also known to activate macrophages, in part, by increasing CD36, and to facilitate the transformation of macrophages to foam cells.…”
Section: Monocyte Migration and Differentiation Of Macrophage And Foamentioning
confidence: 99%
“…TLR4 is the bestcharacterized of the TLR receptors, and was previously reported to be activated by heme in human embryonic kidney-293 or macrophage cell lines (18,22). Thus, to determine whether NFkB and HIF activation in our system was dependent on a TLR4-signaling pathway, HMECs-1 were treated with HbFe 21 , HbFe 31 , HbFe 41 , or LPS (as a positive control) in the presence or absence of a TLR4 inhibitor, TAK-242.…”
Section: Tlr4 Inhibitionmentioning
confidence: 99%
“…TLR receptors are expressed in many cell types, including the vascular endothelium, and play a key role in the innate immune response (17)(18)(19)(20). Nearly all TLRs activate the myeloid differentiation primary response gene-88 (MyD88) pathway that regulates NF-kB (19).…”
mentioning
confidence: 99%